A Daily-Updated Database and Tools for Comprehensive SARS-CoV-2 Mutation-Annotated Trees. (1st September 2021) - McBroome, Jakob; Thornlow, Bryan; Hinrichs, Angie S; Kramer, Alexander; De Maio, Nicola; Goldman, Nick; Haussler, David; Corbett-Detig, Russell; Turakhia, Yatish
Abstract: The vast scale of SARS-CoV-2 sequencing data has made it increasingly challenging to comprehensively analyze all available data using existing tools and file formats. To address this, we present a database of SARS-CoV-2 phylogenetic trees inferred with unrestricted public sequences, which we update daily to incorporate new sequences. Our database uses the recently proposed mutation-annotated tree (MAT) format to efficiently encode the tree with branches labeled with parsimony-inferred mutations, as well as Nextstrain clade and Pango lineage labels at clade roots. As of June 9, 2021, our SARS-CoV-2 MAT consists of 834, 521 sequences and provides a comprehensive view of the virus' evolutionary history using public data. We also present matUtils—a command-line utility for rapidly querying, interpreting, and manipulating the MATs. Our daily-updated SARS-CoV-2 MAT database and matUtils software are available at http://hgdownload.soe.ucsc.edu/goldenPath/wuhCor1/UShER_SARS-CoV-2/ and https://github.com/yatisht/usher, respectively.